Synthesis of 6-(2-Methoxynaphthyl)-2,3-dihydro-1,2,4-triazine-3-thione as a New Reagent for Spectrophotometric Determination of Copper - Maliheh Barazandeh Tehrani; Hutan Ghanbari; Effat Souri; Fazel Shamsa; Mohsen Amini (International Journal of Analytical Chemistry)
A simple, sensitive, accurate, and green spectrophotometric method for the determination of Cu(II) using newly synthesized reagent, 6-(2-methoxynaphthyl)-2,3-dihydro-1,2,4-triazine-3-thione (MNDTT), has been developed. MNDTT was synthesized based on the acylation of methoxy naphthalene and reaction of the product with amyl nitrite, which upon reaction with thiosemicarbazide yielded 6-(2-meyhoxynaphthyl)-2,3-dihydro-1,2,4-triazine-3-thione. MNDTT produces a dark red complex with copper in methanol according to the 1 : 2 stoichiometry. Beer’s law was obeyed over the concentration range of 2.5–20 µg/mL with r2=0.992. The limit of detection and limit of quantification were 0.33 and 1.10 µg/mL, respectively. Within-day and between-day precision values were less than 3.68%. Finally, the method has been applied to a dental alloy (110-plus) successfully and the results were compared with atomic absorption method. The results showed that there was no significant difference between the two methods (P>0.05).